Assessment of the State of Anti-Measles Immunity in Medicine Personnel of a Children's Hospital - T. G. Tkachenko; A. V. Dmitriev; R. A. Gudkov; N. V. Fedina (Эпидемиология и вакцинопрофилактика)
Relevance The epidemiological disadvantage of measles in developed countries reflects the weakening of herd immunity and is caused, first of all, a change in society's attitude to vaccine prevention and the risks of infectious diseases, which requires a revision of the prevention strategyAim: assessment of measles immunity in employees of the regional multidisciplinary children's hospital.Materials & Methods. 365 employees were examined at the same time in 2019 on the basis of the regional children's hospital. Investigation of the intensity of immunity to measles by ELISA using the VectoKor-IgG test system (Vector-Best, Russia). The surveyed were divided into 4 age groups (20–29, 30–39, 40–49 and 50 years and older). Statistical processing was carried out using the χ2 test and Spearman's rank correlation.Results. 63% of the examined had a protective titer of antibodies. The least protected were medical workers under the age of 40, especially up to 30 years old, with a share of immune persons of 30%. In older age groups, the proportion of seropositive persons was 80.9%. The age of the employees and the levels of measles immunity were highly correlated (r = 0.72). There was no statistically significant effect on the state of measles immunity of professional status, the presence of documentary evidence of vaccination.Conclusions. Thus, the results of the conducted study indicate a high epidemiological risk of measles in medical institutions and when applying to them. The worst indicators of protective immunity were found among young employees. It is advisable to continue serological monitoring in medical institutions, organized vaccination of seronegative individuals, as well as conduct cooperative research